2014
DOI: 10.1111/jne.12132
|View full text |Cite
|
Sign up to set email alerts
|

Rapid induction of the Growth Hormone Gene Transcription by Glucocorticoids In Vitro: Possible Involvement of Membrane Glucocorticoid Receptors and Phosphatidylinositol 3‐Kinase Activation

Abstract: The regulation of transcription of the growth hormone (GH) gene by glucocorticoids was studied in MtT/S cells, a cell line derived from an oestrogen-induced mammotrophic tumour in the rat, and in the primary culture of the anterior pituitary gland of adult mice. The levels of the GH heteronuclear RNA (GH hnRNA), which are mainly determined by the transcription rate, increased by 25-fold during 24 h in response to dexamethasone (DEX; 1 μM) in MtT/S cells that were cultured in the medium containing charcoal-stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The activated GR translocate into the nucleus, binds glucocorticoid, and controls specific gene transcription [ 18 ]. In somatotrophs of a normal pituitary gland, GR is possibly involved in the rapid induction of the GH gene transcription by CORT [ 19 ]. Our results show that in ovo administration of exogenous CORT brought about correspondingly identical changes in the expression of membrane GR and GH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activated GR translocate into the nucleus, binds glucocorticoid, and controls specific gene transcription [ 18 ]. In somatotrophs of a normal pituitary gland, GR is possibly involved in the rapid induction of the GH gene transcription by CORT [ 19 ]. Our results show that in ovo administration of exogenous CORT brought about correspondingly identical changes in the expression of membrane GR and GH.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , protein synthesis inhibitors completely inhibited the glucocorticoid-induced GH mRNA expression in both, mice and chick embryonic pituitary cells, suggesting the absence of a direct involvement of glucocorticoid in this process [ 20 , 21 ]. Studies have proved that in vitro , phosphatidylinositol 3-kinase might possibly be involved in the rapid induction of gene transcription of GH by glucocorticoids [ 19 ]. A recent study has demonstrated the involvement of Ras- and ERK 1/2-mediated transcriptional events requiring histone deacetylase activity in the glucocorticoid mediated induction of pituitary GH during chicken embryonic development [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The assessments of the embryonic day were based on the plug date, defined as embryonic day (E)0. The preparation of the monolayer culture of pituitary cells was carried out as described previously with slight modifications. Adult mice were killed by cervical dislocation, and the anterior pituitary glands were removed.…”
Section: Methodsmentioning
confidence: 99%
“…Glyceraldehyde-3-phosphatedehydrogenase ( GAPDH ) mRNA was chosen as the reference gene, and the 2 −ΔΔ C t method was applied to quantify Cyp-D mRNA expression change. The murine Cyp-D mRNA primers were 5’-AGGTGGCGAAAGTATTTATG-3’ and 5’-GGAGTCGGAACTGTTGTGAT-3’ [ 52 ].…”
Section: Methodsmentioning
confidence: 99%